Satellite‐based climatology of low‐level continental clouds in southern West Africa during the summer monsoon season. Issue 3 (10th February 2015) - van der Linden, Roderick; Fink, Andreas H.; Redl, Robert
Abstract Synoptic observations and various satellite products have been utilized for computing climatologies of low‐level stratus over southern West Africa for the wet monsoon seasons July–September of 2006–2011. Previous studies found inconsistencies between satellite cloud products; climate models often fail to reproduce the extensive stratus decks. Therefore, a better observational reference and an understanding of its limitations are urgently needed to better validate models. Most detailed information of the spatiotemporal characteristics of low‐level clouds was obtained from two Meteosat Second Generation (MSG) satellite‐based data sets. However, CALIPSO and CloudSat cross sections of cloud occurrence frequency suggest that both MSG products underestimate the low‐level cloudiness over Nigeria due to shielding by abundant upper level and midlevel clouds and reveal that the stratus is lower over the continent than over the ocean. The Terra Multiangle Imaging Spectroradiometer product appears to overestimate the morning extent of low‐level clouds. The climatology presented here shows that the zone of abundant low‐level stratiform clouds is at its diurnal minimum south of 6–7°N around sunset ( 1800 UTC). Thereafter, it starts to spread inland and reaches its maximum northward extent of 10–11°N between 0900 and 1000 UTC. The maximum affected area is approximately 800, 000 km2. After about 1000 UTC, the northern boundary gets fragmented due to the breakup of stratus decks into fair‐weather cumuli. The stratus is most frequent around Cape Palmas, over Ivory Coast, and at the windward sides of the Mampong Range (Ghana) and Oshogbo Hills (Nigeria).